THE ROLE OF USA IN COMBATING TERRORISM IN AFGHANISTAN, 2016-2020 - Mbaeze, Netchy (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
Events throughout history have been necessitated some response from humankind. One of such major events that appear to have changed the global security scene was the September 11, 2001 attack on the US by an Afghan based terrorist group. This study thereby sets out to study the role of US in combating terrorism in Afghanistan. The set objectives are to examine the impact of terrorism on the political development of Afghanistan; to examine US responses in combating terrorism in Afghanistan. The researcher made use of ex post facto research design. Documentary method of data collection and content analysis were also adopted. The study was anchored on strategic theory. Findings revealed that terrorism has impacted negatively on the political development of Afghanistan. Terrorist activities in Afghanistan have not just destabilized the political system but also made them largely dependent on external forces for their protection. It also revealed that the US response helped in combating terrorism in Afghanistan by dislodged terrorists from major cities thereby reducing incidences of human right abuse. Among others, the researcher recommends an increased international pressure on the Taliban regime to run an all-inclusive government to help stabilize the political system.